Unveiling astrocytic control of cerebral blood flow with optogenetics - Masamoto, Kazuto (Sci Rep, 2015)
Cortical neural activities lead to changes in the cerebral blood flow (CBF), which involves astrocytic control of cerebrovascular tone. However, the manner in which astrocytic activity specifically leads to vasodilation or vasoconstriction is difficult to determine. Here, cortical astrocytes genetically expressing a light-sensitive cation channel, channelrhodopsin-2 (ChR2), were transcranially activated with a blue laser while the spatiotemporal changes in CBF were noninvasively monitored with laser speckle flowgraphy in the anesthetised mouse cortex. A brief photostimulation induced a fast transient increase in CBF. The average response onset time was 0.7 ± 0.7 sec at the activation foci, and this CBF increase spread widely from the irradiation spot with an apparent propagation speed of 0.8–1.1 mm/sec. The broad increase in the CBF could be due to a propagation of diffusible vasoactive signals derived from the stimulated astrocytes. Pharmacological manipulation showed that topical administration of a K(+) channel inhibitor (BaCl(2); 0.1–0.5 mM) significantly reduced the photostimulation-induced CBF responses, which indicates that the ChR2-evoked astrocytic activity involves K(+) signalling to the vascular smooth muscle cells. These findings demonstrate a unique model for exploring the role of the astrocytes in gliovascular coupling using non-invasive, time-controlled, cell-type specific perturbations.